1986
DOI: 10.1111/j.1399-3054.1986.tb05763.x
|View full text |Cite
|
Sign up to set email alerts
|

Which cells respond to gravitropic stimulus in the lentil root?

Abstract: When roots of lentil (Lens culinaris L., cv. Large blonde) were placed in horizontal position for 2 h, their upper side elongated faster than their lower side, and also faster than vertical controls. The length of the cortical cells was greater in the upper half than in the lower half of roots which had been horizontally stimulated for 2 h. The zone of curvature extended from the distal part of the meristem to the proximal part of the cell elongation zone. The curvature in the meristem was due to early differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
1
0
2
Order By: Relevance
“…Les mecanismes de Ia courbure gravitropique sont maintenant mieux connus grace aux analyses morphometriques (Barlow et Rathfelder, 1985 ;Selker et Sievers, 1985 ;Zieschang et Sievers, 1991) ou cytologiques (Darbelley et al, 1986). La croissance cellulaire au niveau du meristeme et de Ia zone d'elongation a ete analysee par Darbel- (Fig.…”
Section: La Reaction Gravitropiqueunclassified
See 1 more Smart Citation
“…Les mecanismes de Ia courbure gravitropique sont maintenant mieux connus grace aux analyses morphometriques (Barlow et Rathfelder, 1985 ;Selker et Sievers, 1985 ;Zieschang et Sievers, 1991) ou cytologiques (Darbelley et al, 1986). La croissance cellulaire au niveau du meristeme et de Ia zone d'elongation a ete analysee par Darbel- (Fig.…”
Section: La Reaction Gravitropiqueunclassified
“…Lorsque l'axe primaire d'une plantule change d'orientation dans Ie champ gravitationnel terrestre, l'extremite racinaire se courbe et se replace dans Ia direction de Ia gravite (Audus, 1962 ;Larsen, 1962 ;Perbal, 1978;Volkmann et Sievers, 1979). La reaction gravitropique resulte d'un phenomene de croissance asymetrique qui s'etablit rapidement dans les moities inferieure et superieure de Ia racine (Barlow et Rathfelder, 1985 ;Darbelley et al, 1986;Selker et Sievers, 1987 ;Zieschang et Sievers, 1991). Ainsi, apres 1 h de stimulation en position horizontale, Ia courbure atteint deja 15 a 20°.…”
Section: Introductionunclassified
“…A variety of changes in growth patterns during the gravitropic response has been reported in different species; these changes are reflected at the cellular level as differential stimulation or inhibition of cell elongation during gravireaction (Pilet and Ney 1981;Barlow and Rathfelder 1985;Darbelley et al 1986). By examining the kinetics of growth rate changes during gravitropism in Lepidium roots (Selker and Sievers 1987) and in maize (Ishikawa et al 1991), it was shown that the pattern of differential growth changes during the gravitropic reaction and involves changes in the position of the elongation zone.…”
Section: Introductionmentioning
confidence: 98%